2015
DOI: 10.18632/oncotarget.4329
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 as a strongest prognosis marker and its downregulation promotes metastasis in colorectal cancer

Abstract: BackgroundConflicting results regarding the role of DEAD-box polypeptide 3 (DDX3) are seen not only between cancer types but also within the same type of cancer. In this study, we aimed at clarifying the prognostic significance of DDX3 in patients of major cancer types through large cohort survival analysis and further investigated its effects on cancer progression.MethodsLarge cohort survival analysis of 7 cancer types, including colorectal cancer, breast cancer, lung cancer, head and neck cancer, liver cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 32 publications
2
31
1
Order By: Relevance
“…Although there are some controversial data indicating that DDX3 is a tumor suppressor (3941), it is possible that the function of DDX3 is organ-specific. Our previous data in lung cancer indicate that inhibition of DDX3 function by a small-molecule inhibitor, RK-33, reduces cell proliferation in lung cancer and radiosensitizes lung cancer cells in a DDX3-dependent manner (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some controversial data indicating that DDX3 is a tumor suppressor (3941), it is possible that the function of DDX3 is organ-specific. Our previous data in lung cancer indicate that inhibition of DDX3 function by a small-molecule inhibitor, RK-33, reduces cell proliferation in lung cancer and radiosensitizes lung cancer cells in a DDX3-dependent manner (19).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that DDX3 acts as a tumor suppressor in colorectal cancer. Knockdown of DDX3 increases cancer progression through Snail/E-cadherin pathway in colon cancer cells (36). In addition, colorectal cancer patients with low DDX3 expression have poor prognosis and more frequent distant metastasis (36).…”
Section: Ddx3 Role In Cancer: Tumor Suppressor or Oncogenementioning
confidence: 99%
“…DDX3 knockdown downregulates Snail levels and decreases cell proliferation and migration in breast cancer MCF-7 cells (47). However, the inhibition of DDX3 induces the EMT process, with upregulation of Snail and decrease of E-cadherin in colorectal cancer DLD-1 and HCT116 cells (36).…”
Section: Multifunctions Of Ddx3-mediated Signaling Pathwaysmentioning
confidence: 99%
“…For instance, most of the recent studies demonstrated that DEAD-box RNA helicase 3 (DDX3) acts as an oncogenic role in breast cancer (Bol et al, 2013) , but some studies (Su et al, 2015) ( Zhao et al, 2016) also showed that its downregulation promotes metastasis in colorectal cancer indicating a potential role as TSG.…”
Section: Introductionmentioning
confidence: 99%